2013
DOI: 10.1007/s11060-013-1054-1
|View full text |Cite
|
Sign up to set email alerts
|

Primary brain tumour epidemiology in Georgia: first-year results of a population-based study

Abstract: A population-based cohort study was initiated in Georgia in March 2009 to collect epidemiologic data of malignant and non-malignant primary brain tumours. During the first year, 473 incident cases were identified. For a population of 4.3 million, the annual incidence rate was 10.25 per 100,000 inhabitants, age-standardized to the year 2000 US population. Non-malignant tumours constituted about 66 % of all tumours. Males accounted for 40 % and females for 60 % of the cases. Crude incidence rates by histology we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
2
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 11 publications
1
21
2
2
Order By: Relevance
“…In contrast, Korea in 2005 and Georgia in 2009 have shown a predominance of meningeal tumours (30% and 29.81% respectively) among diagnosed CNS tumours. In the present study we have found a prevalence of neuroepithelial tumours (~40%), which contrasts with the distribution of CNS tumour types elsewhere [10,12,15,16]…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast, Korea in 2005 and Georgia in 2009 have shown a predominance of meningeal tumours (30% and 29.81% respectively) among diagnosed CNS tumours. In the present study we have found a prevalence of neuroepithelial tumours (~40%), which contrasts with the distribution of CNS tumour types elsewhere [10,12,15,16]…”
Section: Discussioncontrasting
confidence: 99%
“…The first year results of the study have been reported recently [2]. We performed the analysis of two years data in order to increase the statistical power.…”
Section: Introductionmentioning
confidence: 99%
“…Glioma belongs to the most common primary malignant brain tumor (astrocytic, oligodendroglial, oligoastrocytic and ependymal origin) (Ostrom et al, 2011;Gigineishvili et al, 2013). It accounts for almost 80% of primary malignant brain tumors, usually leading to poor survival compared to other types of brain tumors (Bondy et al, 2008).…”
Section: Introductionmentioning
confidence: 99%